2017
DOI: 10.4236/ojog.2017.77079
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Thyroid Disease and Neonatal Low Birth Weight: A Systematic Review and Meta-Analysis

Abstract: Objective: Thyroid disorder is a common endocrine complication in pregnant women: the association between neonatal low birth weight (LBW) and thyroid dysfunction during pregnancy has not been definitely confirmed. We conduct a systematic literature review and meta-analysis of the adverse fetal complication of LBW in maternal thyroid disease, including overt and subclinical hyperthyroidism and hypothyroidism. Methods: Relevant studies in English published between 1990 and 2016 were identified by searching PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Studies published after the publication of the 2017 ATA-GL report contradictory results. On one hand, there were meta-analyses that did not report an impact on IUGR and LBW ( 8 , 13 , 14 ), and on the other hand, original studies and meta-analyses reporting a higher prevalence of PTB ( 3 , 5 ), pre-eclampsia ( 7 ), placental abruption and even a lower risk of abortion ( 6 ). These more recent studies also included women with sTSH levels (and thus not only with low TSH) and considered demographic and obstetric confounders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies published after the publication of the 2017 ATA-GL report contradictory results. On one hand, there were meta-analyses that did not report an impact on IUGR and LBW ( 8 , 13 , 14 ), and on the other hand, original studies and meta-analyses reporting a higher prevalence of PTB ( 3 , 5 ), pre-eclampsia ( 7 ), placental abruption and even a lower risk of abortion ( 6 ). These more recent studies also included women with sTSH levels (and thus not only with low TSH) and considered demographic and obstetric confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Since the ATA publication in 2017, other studies have associated SH with an increased prevalence of preterm delivery (PTB) ( 3 , 4 , 5 ), pre-eclampsia ( 6 , 7 ) and low birth weight ( 3 ). On the contrary, a meta-analysis did not associate SH with a low-birth weight ( 8 ).…”
Section: Introductionmentioning
confidence: 89%
“…Three meta-analyses assessed the adverse pregnancy outcomes in women with subclinical hyperthyroidism. These studies had mainly focused only on preterm delivery, IUGR, and LBW and found no significant association between subclinical hyperthyroidism and these outcomes ( 25 , 30 , 50 ). This meta-analysis of nine studies demonstrated that subclinical hyperthyroidism was not associated with adverse maternal outcomes, such as hypertensive disorders, preterm delivery, and pregnancy loss, neonatal outcomes, such as macrosomia/LGA, and adverse fetal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous systematic reviews and meta-analyses have been published on adverse pregnancy outcomes of thyroid dysfunction so far (8,25,(28)(29)(30)(31); however the majority of them have not reported these outcomes specifically for subclinical hyperthyroidism (8,28,29). Among those ones that included this subgroup of thyroid dysfunction, various feto-maternal outcomes have not been investigated and only intrauterine growth restriction (IUGR) (25) and low birth weight (LBW) (30) have been reported.…”
Section: Contextmentioning
confidence: 99%
“…However, in studies conducted by Khetua et al, 19 S. Pachauri et al, 22 and Shanti Ghosh et al, 23 it was concluded that maternal haemoglobin played a important role in the neonatal birth weight. In a systemic review and meta-analysis conducted by Gin Chiu et al, 24 it was concluded that hyperthyroidism in pregnancy was associated with a higher increased risk of LBW infants compared with normal thyroid function in pregnancy, whereas, no association was found between LBW newborns and maternal subclinical hyperthyroidism or hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%